Identification of drivers' driving habits and shift schedule correction for vehicles with automatic transmission. (April 2022) - Xia, Guang; Zhang, Hualei; Tang, Xiwen; Wu, Shilong; Zhao, Linfeng; Hu, Jinfang
Resource conservation has become a hot topic, and driving habits also have a significant impact on a car's fuel consumption. In view of the different needs of drivers with different driving habits for automatic transmission and shift characteristics, a vehicle automatic transmission, and shift correction control strategy based on driving habit recognition is proposed. Based on the analysis of drivers' driving behavior, the phase space reconstruction method is first used to reconstruct the time series of driving control signals, and the driving habit identification and gear shift correction control are conducted based on the correlation dimension and Kolmogorov entropy evaluation index. Simulation and real car test show that the identification method based on phase space reconstruction method and driving habits evaluation index can accurately identify drivers' driving habits. The gear shift correction control strategy based on driving habit recognition fully meets the different requirements of different drivers for the gearshift performance of vehicles and improves the intelligence degree of automatic transmission of vehicles.